RhoA/Rho kinase mediates TGF-β(1)-induced kidney myofibroblast activation through Poldip2/Nox4-derived reactive oxygen species - Manickam, Nagaraj (American Physiological Society, 2014)
The small G proteins Rac1 and RhoA regulate actin cytoskeleton, cell shape, adhesion, migration, and proliferation. Recent studies in our laboratory have shown that NADPH oxidase Nox4-derived ROS are involved in transforming growth factor (TGF)-β(1)-induced rat kidney myofibroblast differentiation assessed by the acquisition of an α-smooth muscle actin (α-SMA) phenotype and expression of an alternatively spliced fibronectin variant (Fn-EIIIA). Rac1 and RhoA are essential in signaling by some Nox homologs, but their role as effectors of Nox4 in kidney myofibroblast differentiation is not known. In the present study, we explored a link among Rac1 and RhoA and Nox4-dependent ROS generation in TGF-β(1)-induced kidney myofibroblast activation. TGF-β(1) stimulated an increase in Nox4 protein expression, NADPH oxidase activity, and abundant α-SMA and Fn-EIIIA expression. RhoA but not Rac1 was involved in TGF-β(1) induction of Nox4 signaling of kidney myofibroblast activation. TGF-β(1) stimulated active RhoA-GTP and increased Rho kinase (ROCK). Inhibition of RhoA with small interfering RNA and ROCK using Y-27632 significantly reduced TGF-β(1)-induced stimulation of Nox4 protein, NADPH oxidase activity, and α-SMA and Fn-EIIIA expression. Treatment with diphenyleneiodonium, an inhibitor of NADPH oxidase, did not decrease RhoA activation but inhibited TGF-β(1)-induced α-SMA and Fn-EIIIA expression, indicating that RhoA is upstream of ROS generation. RhoA/ROCK also regulated polymerase (DNA-directed) δ-interacting protein 2 (Poldip2), a newly discovered Nox4 enhancer protein. Collectively, these data indicate that RhoA/ROCK is upstream of Poldip2-dependent Nox4 regulation and ROS production and induces redox signaling of kidney myofibroblast activation and may broader implications in the pathophysiology of renal fibrosis.